2015
DOI: 10.1007/s00246-015-1191-8
|View full text |Cite
|
Sign up to set email alerts
|

Under-recognition of Low Blood Pressure Readings in Patients with Duchenne Muscular Dystrophy

Abstract: Duchenne muscular dystrophy (DMD), a recessive sex-linked hereditary disorder, is characterized by degeneration, atrophy, and weakness of skeletal and cardiac muscle. The purpose of this study was to document the prevalence of abnormally low resting BP recordings in patients with DMD in our outpatient clinic. The charts of 31 patients with DMD attending the cardiology clinic at Rush University Medical Center were retrospectively reviewed. Demographic data, systolic, diastolic, and mean blood pressures along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Recent clinical studies have called attention to a critical role for low blood pressure in DMD [47À50]. Specifically, low blood pressure in an ambulatory setting emerged as a distinctive feature of DMD patients [47,49,50]. In a retrospective study of 43 DMD patients [48], Cheeran and coworkers identified low systolic pressure as one of the prognostic factors that predicts a worse outcome and death.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies have called attention to a critical role for low blood pressure in DMD [47À50]. Specifically, low blood pressure in an ambulatory setting emerged as a distinctive feature of DMD patients [47,49,50]. In a retrospective study of 43 DMD patients [48], Cheeran and coworkers identified low systolic pressure as one of the prognostic factors that predicts a worse outcome and death.…”
Section: Discussionmentioning
confidence: 99%
“…Duchenne muscular dystrophy (DMD; OMIM#310200), the most severe form of dystrophinopathies, is a lethal X-linked recessive disorder characterized by progressive muscle degeneration, loss of walking ability, decline of respiratory and cardiac function, and early death [ 1 ]. Besides the skeletal and heart muscle [ 2 ], the disease affects other organs such as the central nervous system [ 3 ] and organs which are dependent on smooth muscle function such as the gastrointestinal [ 4 ] and the vascular system [ 5 ]. DMD is caused by mutations in the dystrophin gene ( DMD ) that prevent the expression of functional dystrophin.…”
Section: Introductionmentioning
confidence: 99%
“…A study on the BP of boys with DMD has reported the prevalence and correlations of low BP levels measured at the office with a possible autonomic dysfunction due to DMD. 23 Regarding office BP measurement, more than 50% of the boys had stage 1 or 2 AH, and 12.8% had borderline BP levels. The VII Brazilian Guidelines on Hypertension replaced the term 'borderline' with 'prehypertension', and estimates its prevalence between 10% and 15% of the pediatric population.…”
Section: Discussionmentioning
confidence: 97%